Treaty Relations as a Method of Resolving Intellectual Property Issues (Project Summary) - Michael Asch; Intellectual Property Issues in Cultural Heritage (Simon Fraser University, 2014)
The project summary for "Treaty Relations as a Method of Resolving Intellectual Property Issues", an IPinCH Community Initiative.